The good, the bad, and the very ugly a Hollywood journey - Locke, Sondra 1944-2018 (Morrow, 1997)
Sondra Locke tells the story of her childhood in Tennessee, her career as an actress and director, her relationship and breakup with actor Clint Eastwood, and her experience with breast cancer.
Keywords: Eastwood, Clint <1930->; Locke, Sondra; Locke, Sondra -- 1944-2018; Films; Film; Motion picture actors and actresses -- United States -- Biography; Motion picture producers and directors -- United States -- Biography; Autobiografie; USA; Biografie